Transformational of conventional wafer defect disposition system info web base application to improve manufacturing performance - Mohamed Salleh, Narishah (2013)
Material flow in complex manufacturing environment which consist of few hundred steps is highly dependent on effective information flow. Information flow interruption may impact business operations efficiency that caused higher product lead time and poor product quality performance. High dependence of human intervention to process and transfer the data will lead to late detections of the issues and high product lead time due to inefficient of response process. The objective of the study is to develop an interactive and systematic web based applications which transformed from complex and tedious desktop application system. Web base Information System through integrating data mining with knowledgebase approach is proposed for the automation purpose. The research will be carried out at CDSEM OFF-LINE Station at Penang Seagate Slider Factory. The system will be developed using online Penang Seagate Factory Information System facilities (FIS) with the ORACLE Data Mining and Knowledgebase principles. Experimental approach is developed based on Pre-Test and Post-Test principle to investigate its relative gain to the organization. The result had shown a significant impact with 50% reduction in disposition cycle time, real-time data update and 60% improvement in resources efficiency. Further improvement should be focused to improve the web based features to make the system more efficient in terms of data analysis user friendly functions by expanding the query functions. Integration of the system with the Quality Containment Web system should further evaluated to eliminate human intervention to ensure early containment.